Pengelolaan Usaha Penginapan Hidayah Sambas - Fitriani (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The phenomenon that is the background of this research is the growing development of the sharia-based lodging industry in Indonesia, including in the Sambas area, one of which is Penginapan Hidayah. Although it has implemented sharia principles, this lodging still faces various challenges, such as the lack of promotion and halal certification from the MUI. Therefore, this study aims to determine how sharia lodging is managed at Penginapan Hidayah and the supporting and inhibiting factors that influence the implementation of sharia principles in this lodging business. The method used in this study is a descriptive qualitative approach, with a type of field research. Data collection techniques were carried out through in-depth interviews with the owners and managers of the lodging, direct observation of the lodging operations, and related documentation. The data obtained were analyzed using data analysis techniques from Miles and Huberman, which include data reduction, data presentation, and drawing conclusions. Data validity was tested using triangulation and member check techniques. The results of the study indicate that the management of Penginapan Hidayah has been running well and in accordance with sharia principles in terms of planning, organizing, implementing, and controlling. The main supporting factor is the management's firm commitment to sharia principles, but the main inhibiting factor is the absence of halal certification from the MUI and the lack of promotion that can increase the visibility of the accommodation. Overall, even though it does not yet have a halal certificate, Penginapan Hidayah has implemented sharia principles in its operations and is known as a sharia accommodation in Sambas.